RELATIONSHIP BETWEEN THE INTENSITY OF SOCIAL MEDIA USAGE WITH SLEEP QUALITY - Rizki Alfarizi; Titis Hadiati; Hang G. Asikin; Widodo Sarjana (DIPONEGORO MEDICAL JOURNAL (JURNAL KEDOKTERAN DIPONEGORO), 2020)
Background: Social media has become a part of human daily life, including students. The high intensity of social media usage can affect various aspects of life, one of which is the quality of sleep. The high intensity of social media usage is thought to be related with poor sleep quality. This study analyzes the relationship between the intensity of social media usage and sleep quality. Objective: To know the relationship between the intensity of social media usage with sleep quality in dental students. Method: This research was an observational analytic study with a cross-sectional design. The sample was students of the Dentistry Study Program at Faculty of Medicine, University of Diponegoro (n = 79). The intensity of social media usage was measured using the Social Network Time Use Scale and sleep quality was measured using the Pittsburgh Sleep Quality Index. Measurement of dependent and independent variables was done once at a time. Result: Among respondents, 34,2% were reported using social media with low intensity, 58,2% with average intensity, and 7,6% with high intensity; and 34,2% of respondents had good sleep quality and 65,8% had poor sleep quality. There was a significant relationship between SONTUS scores and PSQI global scores on respondents with the result of p = 0.02 (p <0.05) which indicates that there was a significant linear relationship. Likewise, the relationship between SONTUS scores and gender with the result of p = 0.03 (p <0.05) which also indicates a significant relationship between the two. Conclusion: The intensity of social media usage has a relationship with sleep quality and gender.Keywords: The Intensity of Social Media Usage, Sleep Quality, Social Networking Time Use Scale, Pittsburgh Sleep Quaity Index